When a halt is not a halt: An analysis of off-NYSE trading during NYSE market closures - Chakrabarty, Bidisha; Corwin, Shane A.; Panayides, Marios A. (Journal of Financial Intermediation, 2011)
Though trading halts are a common feature in securities markets, the issues associated with the coordination of these halts across markets are not well understood. In fact, regulations often allow traders to circumvent trading halts through the use of alternative venues. Using a sample of order imbalance delayed openings on the NYSE, we examine the costs and benefits of continued trading on alternative venues when the main market calls a halt. We find that trades routed to off-NYSE venues during NYSE halts are associated with significant price discovery and lead to an improved post-halt trading environment. In addition, limit orders routed through ECNs reflect price-relevant information even prior to the halt, with limit book imbalances decreasing and depth filling in during the halt around the eventual reopening NYSE price. However, these informational benefits come at a substantial cost, as both execution costs and volatility are extremely high on off-NYSE venues during NYSE halts.